Sifat Fisis dan Mekanik Baja Karbon Rendah Dengan Perlakuan Karburizing Arang Sekam Padi ARANG SEKAM PADI - Widodo, Eko; , Dr. Supriyono (2017)
This research is conducted to investigate the influence of the use of carburizing treatment toward the hardness and the microstructure of low carbon steel I the process of pack carburizing. Pack carburizing is mostly used to increase mechanical properties of steel which needs a solid surface but strong inside. In this research,carburizing medium used is 80% of rice husk charcoal and 20% of an active chemical NaCO3. Carburizing process is carried out at a temperature of 9800 with 2 hours detention time. It uses rice husk charcoal and raw material media. The result of the reseach shows that rice husk charcoal medium has 234.674 VHN with an average of 206.869 VHN. The raw material medium has 200.541 VHN an average of 183.817 VHN. The raw material is increased its hardness after being given the carburizing treatment. Therefore,the detention time in carburizing process affects the hardness of the materials.